Peningkatan Literasi AI Dan Python Melalui Pelatihan Berbasis Google Colab Untuk Guru SMA Negeri 16 Pekanbaru - Susi Handayani; Taslim (JCoos: Journal of Community Outreach in Science & Society, 2026)
A training program introducing Artificial Intelligence (AI) to teachers at SMA Negeri 16 Pekanbaru was conducted to enhance participants’ basic understanding and initial skills in applying AI technologies within educational settings. The training covered foundational AI concepts, basic Python programming, and hands-on sessions using Google Colaboratory (Colab) as a cloud-based practical tool. Delivered through a combination of lectures, hands-on practice, interactive discussions, and evaluations (pre-test and post-test), the program involved 20 participating teachers. Evaluation results indicated significant improvement in participants' knowledge, particularly in understanding Python as a programming language for AI, which was grasped by all participants (100%). Meanwhile, comprehension of basic AI concepts and the practical use of Colab reached between 70% and 85%. These outcomes suggest that the training positively contributed to strengthening technological literacy among teachers. Furthermore, this program serves as an initial step in preparing educators for the integration of AI into classroom instruction and highlights the need for ongoing technical support to develop practical AI competencies.